Every Heart Beats True, for the Red, White, and Blue: National Identity Predicts Voter Support. Issue 1 (2nd August 2013) - Ma, Debbie S.; Devos, Thierry
<x xml:space="preserve">Abstract</x> In two studies conducted during the 2012 U.S. presidential election, we sought to determine whether the relative ascription of the American identity to Barack Obama and Mitt Romney was distinct from attitudinal responses and from associations about racial categories. We also tested the degree to which these associations accounted for voter support. In both studies, participants completed a series of Implicit Association Tests and reported their intention to vote for and their willingness to support these candidates. In contrast to implicit associations about racial categories (Black vs. White), Obama was implicitly seen as more American and elicited a more favorable implicit evaluation than Romney (Study 1). At the same time, these effects were reduced when candidates were categorized based on their racial (rather than personal) identity (Study 2). Implicit associations about the candidates (but not racial categories) accounted for intention to vote for them and relative willingness to support them over and above the effect of political orientation (Studies 1 & 2). These findings suggest that the implicit ascription of a national identity is an important facet of presidential elections.